Association between implantable loop recorder use and secondary stroke prevention: a meta-analysis. Issue 1 (16th June 2022) - Huang, Wen-Yi; Ovbiagele, Bruce; Hsieh, Cheng-Yang; Lee, Meng
Abstract : Objective: To conduct a meta-analysis of randomised controlled trials (RCTs) to evaluate the impact of ILR use on occurrence of recurrent stroke. Methods: PubMed, EMBASE, CENTRAL and ClinicalTrials.gov were searched from 1966 to November 2021 to identify RCTs comparing ILR versus non-ILR in patients with ischaemic stroke. Relative risk (RR) with 95% CI was used as a measure of the effect of ILR versus non-ILR on recurrent stroke, recurrent ischaemic stroke, AF detection and oral anticoagulant (OAC) initiation. A fixed-effect estimate based on the Mantel-Haenszel method was computed. Results: We identified three RCTs with 1233 patients with ischaemic stroke. Among three included RCTs, 54 recurrent stroke events were reported in two RCTs and 84 recurrent ischaemic stroke events were reported in three RCTs. Pooled results showed that patients who received ILR versus no ILR was not associated with a significantly reduced risk of recurrent stroke (5.6% vs 8.0%; RR 0.70; 95% CI 0.42 to 1.19) or recurrent ischaemic stroke (5.7% vs 7.9%; RR 0.72; 95% CI 0.48 to 1.10). Compared to non-ILR patients, ILR patients had higher rates of AF detection (12.9% vs 2.4%; RR 5.31; 95% CI, 3.10 to 9.11) and OAC initiation (15.2% vs 5.5%; RR 2.77; 95% CI 1.90 to 4.03). Conclusions: Patients assigned to ILR vs non-ILR did not have a significantly reduced risk of recurrent stroke or recurrent ischaemic stroke despite higher rates of AF detection and OAC initiation. Sufficiently powered RCTs of ILR to assess the risk of recurrent stroke are warranted.